Single‐Atomic‐Co Electrocatalysts with Self‐Supported Architecture toward Oxygen‐Involved Reaction. (9th October 2019) - Xie, Wenfu; Song, Yuke; Li, Shijin; Li, Jianbo; Yang, Yusen; Liu, Wei; Shao, Mingfei; Wei, Min
Abstract: Single‐atomic electrocatalysts (SACs) have shown great promise in electrocatalysis fields owing to their theoretical maximum atom utilization (100%). Yet still, it is far from expectation in practical applications due to entrapping within supports and blocking by aggregation. Herein, self‐supported carbon nanosheet arrays consisting of single‐atomic Co electrocatalyst (SS‐Co‐SAC) toward oxygen‐involved reaction and zinc–air batteries are reported. Impressively, the as‐synthesized SS‐Co‐SAC gives a markedly enhanced utilization of active sites (≈22.3%@2.3 wt%) as a result of single‐atomic dispersion of Co within a unique nanosheet arrays architecture, which is the largest value among other reported results. Benefiting from the high utilization of active sites, the SS‐Co‐SAC electrode exhibits outstanding electrocatalytic performance for both oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). Notably, the turnover frequency value for ORR is determined to be ≈9.26 s −1, which stands for the highest level among noble metal‐free electrocatalysts reported previously. Moreover, as an air‐cathode for zinc–air batteries with SS‐Co‐SAC, a power density of 195.1 mW cm −2 and a robust durability are achieved. It is believed that this study would guide the future design of highly active and durable single‐atom catalysts for both fundamental research and practical applications. Abstract : The self‐supported carbon nanosheet arrays consisting of single‐atomic Co electrocatalyst (SS‐Co‐SAC) with significantly boosted utilization of active sites are synthesized. The as‐prepared SS‐Co‐SAC electrode exhibits outstanding performance for oxygen electrocatalysis and zinc–air batteries, which is expected to open a general pathway to the design of electrocatalysts with much enhanced utilization of active sites.